Current status of tomatoes in Chinese home food gardening: an initial study - Xu, Jingcheng; Liu, Shudong; Qi, Huijuan; Wang, Ying; Gao, Xianyi; Lin, Tingwei; Chen, Jun (Frontiers in Sustainable Food Systems, 2025)
Home food gardening (HFG) is increasingly popular worldwide. Understanding the preferences and challenges of HFG participants holds significant value for the horticulture industry. Tomatoes, a favored ingredient in Chinese cuisine, are particularly popular among Chinese HFG participants. To evaluate their preferences, challenges, and experiences with tomato cultivation, we conducted a survey of 1,296 Chinese tomato growers through social media platforms by using a citizen-science approach, and assessed the germination rates of 400 tomato varieties. The provinces of Guangdong, Jiangsu, and Zhejiang exhibit the highest proportions of home tomato growers, accounting for 18.75, 16.67, and 15.97%, respectively. East China (including Shanghai, Jiangsu Province, Zhejiang Province, Anhui Province, Fujian Province, Jiangxi Province, and Shandong Province) is the region with the highest concentration of growers, accounting for 46.53% of the total. Most respondents fall within the age range of 25 to 39 years (84.03%), with females outnumbering males, comprising 86.11% of the participants. Over 80.00% of respondents have <4 years of cultivation experience. The primary motivation for growing tomatoes is personal or family preference (87.50%). Preferred cultivation sites include rooftops (38.19%) and residential peripheral plots or wasteland (31.94%). Regarding tomato species selection, 60.42% of respondents opt for cherry tomatoes, while double-stem pruning is favored by 39.58%. Tomato yellow leaf curl virus (TY virus) affects 39.58% of growers, and red spider mites impact 45.83%. Fruit cracking during the rainy season is the most prevalent issue, occurring in 66.67% of cases. A significant majority of respondents (95.14%) purchase seeds online, with 22.22% willing to pay over 10 CNY (Chinese Yuan) per seed. Desired seed pack sizes are predominantly 3 to 5 seeds (75.00%) and 6 to 10 seeds (40.97%). Seed mystery boxes are rejected by 79.86% of respondents. Only 40.00% of seeds purchased online demonstrate a germination rate exceeding 80.00%, while 7.50% have a germination rate of 0. Tomatoes are popular in Chinese HFG, and challenges such as pests, diseases, and inconsistent seed quality require attention. To better meet the needs of Chinese HFG participants, it is suggested that seed producers can introduce tomato seeds in small package sizes specifically tailored to their requirements. Additionally, QR codes can be attached to the seed packaging, enabling HFG participants to scan the QR codes and obtain relevant prevention and control techniques for various pests and diseases that may occur during tomato cultivation.